2010
DOI: 10.1590/s1413-81232010000100020
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes do índice de massa corporal em adolescentes de escolas públicas de Piracicaba, São Paulo

Abstract: Resumo O objetivo do presente estudo foi verificar os fatores determinantes do índice de massa corporal (IMC) de adolescentes matriculados nas escolas públicas de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
2
0
7
Order By: Relevance
“…Some authors found higher prevalences when their questionnaires included all domains (commuting to work, leisure-time and sports) and different environments of physical activity (inside or outside school) when compared with other studies that excluded some domains or activities at school. For example, some authors defined physical activity as the practice of sports outside school as well as going to school by bike or walking 26,27 . Other authors considered any kind of vigorous and/or moderate physical activity, inside or outside school, in a structured way or not 28,29,30,31,32,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found higher prevalences when their questionnaires included all domains (commuting to work, leisure-time and sports) and different environments of physical activity (inside or outside school) when compared with other studies that excluded some domains or activities at school. For example, some authors defined physical activity as the practice of sports outside school as well as going to school by bike or walking 26,27 . Other authors considered any kind of vigorous and/or moderate physical activity, inside or outside school, in a structured way or not 28,29,30,31,32,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…No presente estudo, a diferença no comportamento da idade cronológica em relação à prevalência de excesso de peso entre meninos e meninas pode ser explicada devido ao fato da maturação sexual variar de maneira mais evidente, cronologicamente, nas meninas do que nos meninos 18 , inferindo-se que em cada faixa etária pode haver maior número de meninas com diferentes estágios de maturação, comportamento esse, observado em menor proporção nos meninos. Esta observação reforça a importância de se verificar, quando necessário, o excesso de peso relativo, também, aos estágios de maturação sexual, fato que já vem sendo destacado na literatura 22,25 , e não somente à idade cronológica, como verificado na maioria dos estudos.…”
Section: Característicasunclassified
“…Para coleta dos dados foi utilizado o instrumento Questionário de Atividade Física para Adolescentes (QAFA) validado através dos estudos de Florindo e colaboradores 11 , sendo sua validade e reprodutibilidade em adolescentes brasileiros confirmadas em estudos posteriores [12][13][14] . Através da ficha do aluno, cedida pelas escolas participantes foram coletados ainda dados como: idade, gênero, escolaridade, surdez ou ausência desta.…”
Section: Métodosunclassified